NARASI OBJEKTIVASI PEREMPUAN DALAM NOVEL PEREMPUAN BATIH KARYA A.R. RIZAL - Kholidatul bahiyah (BASA Journal of Language & Literature, 2023)
Women with various problems are very interesting to be discussed in studying a topic of discussion, because women are often marginalized. This becomes the cause and effect of the occurrence of various forms of a woman's struggle to maintain her existence and attracts it to become a topic of discussion. There are three scopes of aspects that are the focus of research related to the objectivation narrative of women in the novel Batih Women by A.R. Rizal, namely: (1) The objectivation narrative of women's existence in the novel Perempuan Batih by A.R. Rizal, (2) The objectivation narrative of women's position in the novel Perempuan Batih by A.R. Rizal, and (3) The objectivation narrative of the role of women in the novel Perempuan Batih by A.R. Rizal. This study aims to describe the objectivation narrative of women's existence in the novel Perempuan Batih by A.R. Rizal, describes the objectivation narrative of women's position in the novel Perempuan Batih by A.R. Rizal, and describes the objectivation narrative of the role of women in the novel Perempuan Batih by A.R. Rizal. Based on the results of the research, it shows that the objectivation narratives of women are divided into, 1) the objectivation narratives of women's existence which consist of views on the differences in women's positions, women's violence in terms of service in marriage, and women as men's subordinates. 2) narrative objectivation of women's position which consists of position as an individual, position in the family sphere, and position in the community sphere. 3) objectivation narratives of women's roles consisting of women's roles from a biological or environmental tradition and women's roles from their position as individuals and not as husband's assistants.